Environmental education and research in southern Africa: a landscape of shifting priorities - Van Rensburg, Eureta Janse (Rhodes University, Faculty of Education, Department of Education, 1995)
What has come to be labelled as 'the environment crisis' has roots in the structures and orientations of modern societies. True to our modernist ways we call on, or offer, education and research, experts and science, to address our socio-ecological concerns. This study set out to identify research priorities in environmental education from within the institutional setting of a university and within the context of environmental and political change in southern Africa and epistemological shifts in educational research traditions. The emergent research design allowed for a progressive clarification of theoretical vantage point: from an instrumental listing of priorities, through the participatory development of a critical and consensual framework for research, to a reflexive description of a landscape of shifting priorities. I collected data over a 3-year period, in inter alia 38 semi-structured interviews, workshops with some 150 participants, focus group discussions, documents and conferences. Participants' professional contexts included environmental education, natural resource management, social and biophysical sciences, development, formal and non-formal education, funding agencies, academic and non-academic settings. My engagement with the emerging discourses revealed patterns and inconsistencies in participants' views on research, environmental education, change and research priorities. I identified three orientations - Research for Management to Restore Order to Nature and Society, Research to Resolve Practitioners' and Communities' Problems, and Research for Radical Reconstruction - in the emerging landscape. These orientations were accompanied by change models and themes (discourses of difference and 'othering', instrumental views of education and research and accumulative knowledge, a conceptual theory-practice gap) which limited their potential for transformation towards sustainable living. They presented solutions cut from the same modernist cloth as the environment crisis. An emerging Reflexive perspective in and on environmental education research showed potential as a transitionary orientation outside modernist assumptions. I outline research priorities from this perspective. Reflexivity reveals the myths of expert-driven, instrumental and institutionalised research separated from environmental education and based upon rationalistic interpretations of science. It opens up possibilities for transformative knowledge emerging from 're-search' based versions of education as a process of, rather than a means to, social change.
Keywords: Environmental education -- Research -- South Africa; Environmental sciences -- Study and teaching (Higher) -- South Africa